Linguistic features of different proficiency learners’ oral performance in a project-based learning context - Zhong, Jianer; Ismail, Lilliati; Khaiessa Ahmad, Norhakimah (Arab World English Journal (AWEJ), 2024)
Project-Based Learning (PBL) can potentially enhance learners’ oral proficiency. However, little evidence supports how PBL improves learners’ complexity, accuracy, and fluency, particularly for learners with different proficiency levels. This study examined the changes and linguistic features of varying proficiency learners’ complexity, accuracy, and fluency within a PBL context. It involved a homogeneous group of 45 Chinese college learners, categorized into high (N=15), medium (N=15), and low proficiency learners (N=15). Their oral complexity, accuracy, and fluency were assessed using speaking tests before and after PBL. The changes in their oral performance were evaluated using objective measures of complexity, accuracy, and fluency. The transcripts were also used to analyze the linguistic features of different proficiency learners. The results indicate that PBL significantly enhances syntactic complexity as learners’ proficiency levels increase. Significant differences were observed in lexical complexity, pronunciation accuracy, and self-repairs between high and low-proficiency learners. However, no significant differences were found in syntactic accuracy and speech rate across high, medium, and low proficiency learners. The findings also indicate that different proficiency learners reveal various linguistic features of syntactic complexity, syntactic accuracy, and self-repairs in their oral performance. This study provides implications for educators to design project-based activities for different proficiency learners to improve their complexity, accuracy, and fluency.